2021
DOI: 10.1038/s41598-021-90151-4
|View full text |Cite
|
Sign up to set email alerts
|

Monolingual and bilingual language networks in healthy subjects using functional MRI and graph theory

Abstract: Bilingualism requires control of multiple language systems, and may lead to architectural differences in language networks obtained from clinical fMRI tasks. Emerging connectivity metrics such as k-core may capture these differences, highlighting crucial network components based on resiliency. We investigated the influence of bilingualism on clinical fMRI language tasks and characterized bilingual networks using connectivity metrics to provide a patient care benchmark. Sixteen right-handed subjects (mean age 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…network stability through the progressive removal of links until architectural collapse (Morone et al, 2019). Application of these techniques has shown that pre-SMA, PreMA, and BA are part of a frontal "core" of the human language network (Li et al, 2020) that is tightly connected to WA and remains consistent across healthy patients regardless of their spoken language (Li et al, 2021).…”
Section: The Functional Language Network From Tb-fmrimentioning
confidence: 99%
See 1 more Smart Citation
“…network stability through the progressive removal of links until architectural collapse (Morone et al, 2019). Application of these techniques has shown that pre-SMA, PreMA, and BA are part of a frontal "core" of the human language network (Li et al, 2020) that is tightly connected to WA and remains consistent across healthy patients regardless of their spoken language (Li et al, 2021).…”
Section: The Functional Language Network From Tb-fmrimentioning
confidence: 99%
“…brain tumors, fMRI is primarily used for language dominance (Brennan et al, 2016) although the same technique can also provide insights into brain connectivity (Bullmore and Sporns, 2009;Li et al, 2020Li et al, , 2021. Similarly, stroke patients rarely undergo fMRI in clinical practice, foregoing useful information to understand functional deficits and to provide individualized rehabilitation (Kiran and Thompson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Graph theory is applied to fMRI to study the architecture and complexity of functional networks [ 9 , 10 ] with relevant clinical applications [ 11 ]. Newly diagnosed gliomas demonstrated globally altered functional connectomic profiles in previous studies [ 12 ], while distributed changes of the functional connectome have been shown in glioblastoma patients after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each measure characterizes many different features providing a powerful means to classify and predict several brain disorders. The application of graph theory to clinical neuroscience studies shed light on the basic organization of the brain (Supekar et al, 2008;Smith et al, 2011;Li et al, 2020Li et al, , 2021. Also, hypo-and hyper-connectivity may represent biomarkers for different diseases (Bassett et al, 2008;Kocevar et al, 2016;Li et al, 2019;Mazrooyisebdani et al, 2020;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%